2017
DOI: 10.3389/fphys.2017.00735
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Odorant Binding Proteins in the Forelegs of Adelphocoris lineolatus (Goeze)

Abstract: The chemosensory system is essential for insects to detect exogenous compounds, and odorant binding proteins (OBPs) play crucial roles in odorant binding and transduction. In the alfalfa plant bug Adelphocoris lineolatus, an important pest of multiple crops, our understanding of the physiological roles of antenna-biased OBPs has increased dramatically, whereas OBPs related to gustation have remained mostly unexplored. In this study, we employed RNA sequencing and RACE PCR methods to identify putative OBPs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 90 publications
(121 reference statements)
2
32
0
Order By: Relevance
“…These chemosensory associated proteins are usually also expressed in insect legs. By transcriptome sequencing, OBPs, CSPs, SNMPs, GRs, and ORs were identified in the legs of Apis cerana cerana, Ectropis obliqua, and Adelphocoris lineolatus (Ma et al, 2016;Sun et al, 2017;Du et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These chemosensory associated proteins are usually also expressed in insect legs. By transcriptome sequencing, OBPs, CSPs, SNMPs, GRs, and ORs were identified in the legs of Apis cerana cerana, Ectropis obliqua, and Adelphocoris lineolatus (Ma et al, 2016;Sun et al, 2017;Du et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the distribution of these genes not only in the antennae but also in the legs suggests a transport function, probably for chemicals related to mate and/or host recognition. This has been reported for the Lucerne bug, Adelphocoris lineolatus , in which OBP11 showed both significant foreleg‐biased expression and localization in the sensilla chaetica of the forelegs through immunolocalization experiments (Sun et al ., ). This suggests that OBP11 has a gustatory function owing to its binding affinity to bitter compounds, such as quercetin and catechin (Sun et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Notably, most OBPs are expressed in antennae, which indicating the important functions of OBPs in antennal identification processes, such as in C. kiangsu (Li, Jiang & Dong, 2018), H. assulta (Jin et al, 2015) and C. suppressalis (Xia et al, 2015). AlinOBP11 is expressed in the tarsal gustatory sensilla of Adelphocoris lineolatus (Sun et al, 2017a). Expression profiling showed that three CobdPBPs were more highly expressed in males than females and two exhibited significantly higher expression in males, indicating the sex biased expression of CobdPBPs, similar to Conopomorpha sinensis (Li et al, 2018); thus, these proteins may function in male binding of female-emitted pheromones.…”
Section: Discussionmentioning
confidence: 99%